The Role of Arbitrators in the International Context. The Spanish Perspective through Case Law - Rodríguez Roblero, María Inmaculada (CUADERNOS DE DERECHO TRANSNACIONAL, 2026)
This paper analyses arbitration as a legal institution in the Spanish context, through an assessment of case law. To this end, it examines what arbitrability is, who the arbitrator is and what requirements they must meet; how they should conduct themselves and manage the proceedings; and the responsibilities that their task entails. It also mentions the types of arbitration, with special mention of institutional arbitration and its advantages for the correct and efficient resolution of disputes.